THE USE OF CROSSWORD PUZZLE GAME TO IMPROVE STUDENTS’ UNDERSTANDING OF HOMOPHONE - El Garcia Manus; Nurmin Samola; Sanerita T. Olii (Program Studi Pendidikan Bahasa Inggris, 2022)
The background of this research was based on students’ difficulties in differentiating meaning and spelling of the words with homophone pair, which means their understanding of homophone were less. This research is intend to see whether Crossword Puzzle Game is effective or not in improving the students’ ability of understanding homophone. In other words, this research was to find out how much the improvement of students’ understanding after being taught using Crossword Puzzle Game. For that reason a strategy must be given to make them learn easily. In this research, Crossword Puzzle Game was used to help students understand homophone words. This study was focused on writing skill, especially on spelling, at the 7th grade of SMP Negeri 5 Manado, specifically class 7.7, in the academic year of 2021/2022. This research discuss about the use of Crossword Puzzle Game to improve students’ understanding of homophone. The implementation of Crossword Puzzle Game in teaching homophone was conducted with pre-test and post-test. The participant of the pre-test was 22 students where the average of students’ score was 63.77, while the participant of post-test was 21 students where the average of students’ score was 81.52. By those results, the increase percentage was calculated and the result showed that the students’ of 7.7 in SMP Negeri 5 Manado, in the academic year of 2021/2022 made an improvement score about 30.70%. From the description above, the conclusion of this study was the use of Crossword Puzzle Game could improve students’ understanding of homophone.